2018
DOI: 10.1038/s41598-018-33092-9
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa whole grain diet compromises the changes of gut microbiota and colonic colitis induced by dextran Sulfate sodium in C57BL/6 mice

Abstract: A plethora of evidence highlights that the dysbiosis of gut microbiota is a critical factor for inflammatory bowel disease (IBD). Both in vivo and in vitro studies have demonstrated that quinoa possesses potential prebiotic effects. The present study aims to examine the potential in using quinoa to ameliorate the dysbiosis and colitis induced by dextran sodium sulfate (DSS). A total of 40 C57BL/6 mice were fed either an AIN-93M diet or a quinoa-based diet, separately. Colitis was induced for 10 animals/dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 37 publications
4
38
0
2
Order By: Relevance
“…The enrichment of Lachnospiraceae _NK4A136 (around 3.5 folds) was identified in the DSS group compared with the normal group (around 3.0 folds of increase). Findings from current studies of Lachnospiraceae _NK4A136 abundance in IBD model are still a controversy ( Xiao et al, 2016 ; Liu et al, 2018 ; Li M. et al, 2019 ; Li P. et al, 2019 ). Some of them illustrated that an increased abundance of Lachnospiraceae _NK4A136 contributes to alleviate inflammation in IBD model; however, that is not supported by our observation in the present study ( Liu et al, 2018 ; Li M. et al, 2019 ; Li P. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…The enrichment of Lachnospiraceae _NK4A136 (around 3.5 folds) was identified in the DSS group compared with the normal group (around 3.0 folds of increase). Findings from current studies of Lachnospiraceae _NK4A136 abundance in IBD model are still a controversy ( Xiao et al, 2016 ; Liu et al, 2018 ; Li M. et al, 2019 ; Li P. et al, 2019 ). Some of them illustrated that an increased abundance of Lachnospiraceae _NK4A136 contributes to alleviate inflammation in IBD model; however, that is not supported by our observation in the present study ( Liu et al, 2018 ; Li M. et al, 2019 ; Li P. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…also reported that, a high-grain diet dynamically increased the relative abundance of Clostridium_sensu_stricto_1 and induced mucosal injuries in the colon of sheep. Quinoa consumption has been reported (Liu et al, 2018) to significantly alleviate DSSinduced dysbiosis as indicated by decreased abnormal expansion of the phylum Proteobacteria and decreased overgrowth of the genus Peptoclostridium. We also found that the abundances of Enterococcus, Peptoclostridium, and Veillonella were significantly different between the antibiotics-free group and the control group, which indicated that antibiotics have a great influence on the intestinal flora of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in specific taxa, the richness and diversity of gut microbiota are often significantly altered by HF diets (Daniel et al, 2014; Liu et al, 2018) or different drug interventions (Li et al, 2017; Song et al, 2017). The gut microbiota is a major environmental factor that can influence metabolic modifications in the host organism (Ley et al, 2006); it is involved in very important aspects of metabolism, such as vitamin metabolism (Ramakrishna, 2013), SCFA metabolism (Kimura et al, 2013), neuropeptide response (Frohlich et al, 2016), and food digestion.…”
Section: Discussionmentioning
confidence: 99%